The Impact of the Healthy and Nutritious Food Program on Gross Motor Development in 2-3 Year Old Children at Abdurrahman Bin Auf Kindergarten, East Jakarta - Haryani, Annisa Dwi; Riza, Eva (LPPM Universitas Mohammad Husni Thamrin, 2025)
Gross motor development of children is very important for the survival of children because if it is disturbed, the child will experience inhibition of the child's movement which is influenced by the nerve muscles themselves, for example walking, running, jumping and others. Gross motor development can develop well and optimally if the food intake we eat is balanced and fulfilled, therefore the importance of providing nutritional intake. This study aims to determine the impact of a healthy and nutritious food program on the gross motor skills of children aged 2-3 years at Abdurrahman Bin Auf Kindergarten, East Jakarta. Gross motor development in early childhood is an important aspect that is closely related to physical readiness, health, and the child's ability to carry out daily activities. The results of the study indicate that a healthy and nutritious food program has a significant positive impact on children's gross motor skills, including balance, coordination, and specific abilities such as walking, running, and jumping. This study uses a qualitative method with a case study approach. This study involved interviews with the principal, teachers, and parents, as well as direct observation of children's gross motor skills. The study results showed that children who participated in a healthy and nutritious food program had better gross motor skills than those who did not. This study recommends that healthy and nutritious food programs be continued and enhanced to improve gross motor skills in children aged 2-3 years.